Effects of the feeding protocol during blood transfusion on splanchnic tissue oxygenation and complications in very premature infants - He, Jianghua; Sun, Xueshi; Xu, Xiaoming; Luo, Hanwen; Tang, Jun; Xiong, Tao; Zhao, Jing; Shi, Jing (Frontiers in Nutrition, 2024)
Background The effects of blood transfusions on splanchnic oxygenation and complications related to blood transfusions, including red blood cell (RBC) transfusions, in premature infants undergoing enteral feeding, to provide clinical evidence for a management protocol for premature infants during the peri-transfusion period. Methods This single-blind, randomized, controlled trial enrolled sixty eligible preterm infants who were randomly divided into the withholding feeding group (n = 30) or feeding group (n = 30). Enteral feeding was withheld for 8 h, beginning from the start of transfusion infants in the feeding group were fed according to the pre-transfusion feeding approach during and after RBC transfusion. Results Baseline characteristics of those in the withholding and feeding groups were as follows: gestational age (weeks) 27.52 (24.86–30.14) and 27.13 (25.43–30.14); birth weight (g), 1,027 (620–1,450) and 1,027 (620–1,270); blood transfusion day, 48 (14–79) and 39 (10–78); and hemoglobin before blood transfusion (g/L), 81.67 (±10.56) and 85.93 (±14.77). No significant differences were observed between groups at baseline. No significant differences were observed in the average splanchnic tissue oxygenation changes or clinical results at any time. One patient in the withholding feeding group experienced transfusion-associated necrotizing enterocolitis. Conclusions No differences in splanchnic oxygenation observed these feeding protocols. This study suggests the feasibility of a sizable trial to evaluate clinical outcomes. The risks of mesenteric ischemia and transfusion-related necrotizing enterocolitis for premature infants were not increased by enteral feeding during RBC transfusion. Clinical trial registration ChiCTR2200055726 (https://www.chictr.org.cn/).